Internationalization in a post-Soviet state: The impact of global rankings on university messaging in Uzbekistan - Rothwell, Hannah; Smotherson, Brittany; Sofianova, Irina (Journal of International Students, 2026)
The pursuit of global rankings is a hallmark expression of internationalization in higher education. Critical Internationalization (CI) exposes the power relations embedded in these processes, yet their discursive effects in post-Soviet and transitional systems remain insufficiently examined. This study analyzes how universities in Uzbekistan negotiate internationalization pressures by examining the representation of global ranking criteria in discourse. Drawing on Critical Discourse Analysis of university websites, it identifies differences between institutions included in the Times Higher Education (THE) World University Rankings and comparable universities seeking entry. Ranked institutions consistently present ranking-aligned indicators for international audiences, whereas unranked universities privilege locally oriented communication. The findings suggest that global rankings operate not only as evaluative mechanisms but also as normative discursive templates shaping institutional self-representation. The study extends CDA and CI scholarship by demonstrating how ranking regimes structure discourse, while highlighting risks of selective transparency and performative internationalization for policymakers and institutional leaders.